FIRST REPORT OF BLACK ROT OF CARROT CAUSED BY ALTERNARIA RADICINA IN PAKISTAN - S. Javed; A. Javaid (Journal of Animal and Plant Sciences, 2020)
Dry, black, decayed and sunken lesions of fungus were observed on the surface of infected carrot (Daucus carota L.) roots collected from Lahore, Pakistan. The obtained samples were cultured on potato dextrose agar medium in order to obtain the pure fungal colonies and to confirm their pathogenicity by inoculating the fungal mycelia on asymptomatic carrots. On the basis of growth rate, cultural and conidial morphology, the fungus was identified as Alternaria radicina Meier, Drechsler & Eddy. Identification of the isolated fungus was further confirmed by rDNA sequencing and the obtained PCR product was deposited in the GenBank with LT799973 accession number. As per our knowledge this is the first report of black rot of carrot in Pakistan.
Keywords: Alternaria radicina; black rot; causal agent; Daucus carota